1976
DOI: 10.1149/1.2132915
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxidation of GaAs in Mixed Solutions of Glycol and Water

Abstract: Die Titelmethode (Elektrolyt: Propylenglykol + wäßrige 3%ige NH4OH‐gepufferte Weinsäurelösung) ist der herkömmlichen Anodisierung in wäßrigen Lösungen ohne Glykol wesentlich überlegen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(101 citation statements)
references
References 6 publications
7
87
0
7
Order By: Relevance
“…After the onset of anodic current, the cyclic voltammograms behaved in a fashion similar to Fig.1. Namely, they showed a peak and hysteresis, indicating the occurrence of the so-called active-passive transition [15]. At small overpotentials, active anodic dissolution took place, and at larger overpotentials beyond the peaks, the semiconductor surface was covered with a passive oxide film, leading to passivation with nanopore formation as discussed later.…”
Section: Wet Etching and Behavior Of N-inp Anodesmentioning
confidence: 85%
See 2 more Smart Citations
“…After the onset of anodic current, the cyclic voltammograms behaved in a fashion similar to Fig.1. Namely, they showed a peak and hysteresis, indicating the occurrence of the so-called active-passive transition [15]. At small overpotentials, active anodic dissolution took place, and at larger overpotentials beyond the peaks, the semiconductor surface was covered with a passive oxide film, leading to passivation with nanopore formation as discussed later.…”
Section: Wet Etching and Behavior Of N-inp Anodesmentioning
confidence: 85%
“…However, a detailed SEM study has revealed that pores are produced by anodic etching in all of the above three electrolytes. This is distinctly different from the case of viscous eletctrolyte such as aqueous solution of tartaric acid mixed with glycol (AGW electrolyte [15,31]) where uniform anodic oxide films grow in proportion to the overpotential.…”
Section: 1)formation Of Nanoporesmentioning
confidence: 92%
See 1 more Smart Citation
“…Photoenhanced oxidation of n-GaN was carried out in a glycol solution consisting of propylene glycol and 3 wt % tartaric acid at a ratio of 2:1, 22 under potentiostatic control at room temperature, as illustrated in Fig. 1͑a͒.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Typical assumptions for the initial stage of oxidation have been actively discussed for GaAs. Hasegawa et al 22 explained that when the anodic oxide is soluble in the electrolyte, an active-passive transition occurs before surface oxidation. Thus, at the initial stage of the process, oxidation does not occur until the oxidation current exceeds a certain value, j l .…”
Section: A Cyclic Voltammetry Measurement and Oxidation Ratementioning
confidence: 99%